9000 Hours Operation of a 25 Solid Oxide Cells Stack in Steam Electrolysis Mode. (2nd June 2015) - Corre, Gaël; Brisse, Annabelle
Abstract : The operation of 25 solid oxide cells stacks in steam electrolysis mode over 9000 hours is reported. The stack has been operated at current densities of 0.57 and 0.72 A/cm 2, using a 50% steam conversion, in the 750-780°C temperature range. Performance degradation rates of 2.30%/ kh are reported, with some non-homogeneity in the stack repeat units behavior observed. Stack repeat units located at the bottom of the stack feature degradation rates below 2%/kh. The possibility to use the operating temperature as a buffer to counter the performance degradation is highlighted. The stack performance was not affected by incidents that occurred during the test.